Conservación in vitro de germoplasma de Arachis pintoi (Leguminosae) - Rey de Badaró, Hebe Yolanda (2005)
Studies on in vitro storage of either the cytotype diploid (2n=2x=20) or triploid (2n= 3x= 30) ofArachis pintoi were conducted to preserve germplasm under slow-growing conditions. Shoot tips (2-3 mm in length), excised from ín vitro-grown plants, could be effectively maintained for 1 year- in Murashige and Skoog médium (MS) supplemented with 0.01 mg/L NAA. Plants and shoots were regenerated on 83% of the shoot tips cultured. Rooting of the regenerated shoots was achieved by reculturing them on MS + 0.01 mg/L NAA. Subsequent plantlets were then successfully transferred to pots in the greenhouse.